Spoils of war: Trade shocks and segmented labor markets in Spain during WWI - Simon Fuchs (Federal Reserve Bank of Atlanta, 2021)
How does intranational factor mobility shape the welfare effects of a trade shock? I provide evidence that during WWI, a demand shock emanated from belligerent countries and affected neutral Spain. Within Spain, labor predominantly reallocated locally, while the most affected provinces experienced drastic increases in wages and consumer prices. Embedding imperfect labor mobility in an economic geography model, I show that external demand shocks can improve allocative efficiency, but asymmetric shocks cause localized increases in wages and consumer prices instead of reallocation. Adjusting an aggregate gains of trade formula to take domestic reallocation into account more than triples the estimated welfare effects.
Keywords: D5; F11; F12; F15; F16; N9; N14; R12; R13; 330; gains from trade; labor mobility; economic geography